An Amphibious Force for Emerging Demands - Amos, James F (Proceedings - United States Naval Institute, 2013)
Emerging international-security and domestic fiscal environments require the nation's forward-deployed crisis-response forces to aggressively innovate. Additionally, the growing challenge posed by conventional, irregular, and asymmetric threats requires naval expeditionary forces agile enough to adapt as the demands of future naval war fighting, littoral maneuver, and amphibious operations change. Since Pres Thomas Jefferson sent Marines and sailors to fight the Barbary pirates off the coast of North Africa in 1805, US naval forces have been vital to ensuring the national security and economic prosperity. Geographic combatant commanders consistently place high demand on expeditionary forces, and the partners seek to exercise with them to improve their capacity. With guidance in place, the working group set out to design a range of possible force structures, all of which would be subject to both internal and external risk analysis.